Incomplete Outpatient Medical Record Documentation Is Driven by Individual, Organizational, and Psychological Factors: Evidence from a Primary Healthcare Center - Rochim, Nur An Nisyah; Alfiansyah, Gamasiano; Santi, Maya Weka; Erna Selviyanti, Erna Selviyanti (FORIKES, 2026)
Complete outpatient medical records are essential to ensure service quality, patient safety, and administrative efficiency in primary healthcare settings. However, incomplete documentation remains a persistent issue. This study aimed to analyze the factors contributing to incomplete outpatient medical record documentation at a primary healthcare center based on Gibson’s performance theory, encompassing individual, organizational, and psychological factors, and to identify priority problems and improvement strategies. A qualitative study design was employed, with data collected through interviews, observations, documentation review, and brainstorming. Problem prioritization was conducted using the Urgency, Seriousness, Growth (USG) method. The findings revealed that incomplete documentation was influenced by multiple factors. At the individual level, limited work experience and lack of training in medical records were identified. Organizational factors included the absence of control cards, constraints in computer network systems, suboptimal implementation of Standard Operating Procedures (SOPs), and excessive workload beyond core job descriptions. Psychological factors involved the absence of sanctions for incomplete documentation and insufficient attention to detail among staff. Several improvement strategies were proposed, including routine rechecking of record completeness before submission, staff training and supervision, optimization of facility usage, budgeting for electrical system improvements, and regular dissemination and provision of SOPs in each service unit. In conclusion, incomplete outpatient medical record documentation is driven by interconnected individual, organizational, and psychological factors; therefore, comprehensive and targeted interventions are required to improve documentation completeness in primary healthcare settings.Keywords: incompleteness; primary healthcare; medical records; urgency, seriousness, growth (USG)